Hemicentin-1 (Gln5345Arg) Gene Polymorphism in Patients with Essential Hypertension - Srivastava, Kamna; Narang, Rajiv; Bhatia, Jagriti; Saluja, Daman (Cardiology and Cardiovascular Medicine, 2020)
Background: Oxidative stress is one of the risk mechanisms for macular degeneration and essential hypertension. Hemicentin-1 gene was shown to be associated with Age related Macular degeneration, however its role in Essential hypertension has not been reported. We have made the objective to study Hemicentin-1 (Gln5345Arg) gene polymorphism in patients with essential hypertension and the levels of normal protective enzymes such as endothelial Nitric oxide (NO) and malondialdehyde (MDA) in patients with essential hypertension. Methods: The polymorphism of the Hemicentin-1 (Gln5345Arg) gene polymorphism in 250 patient with essential hypertension and 250 controls is studied by PCR-RFLP technique. The plasma levels of MDA and NO were determined using standard procedures. Results: Observed and expected genotypes showed Hemicentin-1 gene variants were conforming to the Hardy–Weinberg equilibrium law. The observed allele frequencies in patients were 0.824 and 0.176 for G and A alleles respectively, whereas 0.896 and 0.104 was observed in controls. Circulating levels of NO was lower in patients with AA genotypes as compared to AG and GG. Lipid peroxidation in terms of levels of circulating MDA was significantly higher in patients with AA genotypes as compared to patients with AG and GG genotypes. Conclusion: There was statistically significant association found between Hemicentin-1 (Gln5345Arg) gene polymorphism and essential hypertension. Individuals with AA genotypes have lower levels of nitric oxide and higher lipid peroxidation as compared to the individuals with AG and GG genotypes indicating that the individuals with AA genotypes may be at substantially higher risk of developing essential hypertension.